Mimicking Transgenerational Signals of Future Stress: Thermal Tolerance of Juvenile Chinook Salmon Is More Sensitive to Elevated Rearing Temperature Than Exogenously Increased Egg Cortisol - Warriner, Theresa R.; Semeniuk, Christina A. D.; Pitcher, Trevor E.; Heath, Daniel D.; Love, Oliver P. (Frontiers in Ecology and Evolution, 2020)
Elevated temperatures resulting from climate change are expected to disproportionately affect ectotherms given their biological function has a direct link to environmental temperature. Thus, as climate change leads to rapid increases in water temperatures in rivers, aquatic ectotherms such as fish may be highly impacted. Organisms can respond to these stressors through flexible and rapid phenotypic change induced via developmental and/or transgenerational plasticity. In oviparous species, gravid females may translate environmental stress across generations via increased exposure of eggs to maternally-derived glucocorticoids (i.e., maternal stress), which has been shown to result in diverse phenotypic effects in offspring. Recent studies suggest these phenotypic changes from maternal glucocorticoids may elicit predictive adaptive responses, where offspring exposed to maternal stress may be better prepared for the stressful environment they will encounter (i.e., environmental match hypothesis). We applied the environmental match hypothesis to examine whether a prenatal exogenous increase in egg cortisol may prepare Chinook salmon offspring (Oncorhynchus tshawytscha) to cope with thermal challenges after being reared in chronically elevated temperatures. Specifically, we exposed eggs to aqueous bath of cortisol-dosed (1000ng/mL) or control (0ng/ml) solutions, and then raised both treatments at current (+0°C—contemporary ambient river temperature) or elevated (+3°C—projected future river temperature) thermal regimes. We quantified thermal performance in fish 7-9 month post fertilization using two methods: via critical thermal maximum (CTMax), and energetic responses (in plasma cortisol, glucose, and lactate) to environmentally relevant, but challenging thermal spikes over 3 days. Overall, we found that exposure to elevated rearing temperatures had a large impact on thermal tolerance, where elevated-temperature reared offspring had significantly higher CTMax. In comparison, egg cortisol treatment had little to no clear effects on CTMax and blood energetic response. Our study demonstrates the importance of elevated water temperatures as an inducer of offspring phenotypes (via early developmental cues), and highlights the significance of examining offspring performance in environments with ecologically relevant stressors.